Innovation systems: Implications for agricultural policy and practice - Hall, A.; Mytelka, L.; Oyeyinka, B. (2005)
Farmers and businesses need to adapt constantly if they are to survive and compete in the rapidly evolving environment associated with the contemporary agricultural sector. Rethinking agricultural research as part of a dynamic system of innovation could help to design ways of creating and sustaining conditions that will support the process of adaptation and innovation. This approach involves developing the working styles and practices of individuals and organizations and the incentives, support structures and policy environments that encourage innovation. Previous efforts to support agricultural sector innovation largely targeted agricultural policy and research organizations. The systems approach recognizes that innovation takes place through the interaction of a broader set of organizations and activities. These patterns of interaction and working styles and practices – or institutions as they are referred to by social scientists – need to adapt continuously if they are to meet the changing demands of the evolving agricultural sector. Institutional learning is central to this process and will ensure research organizations remain relevant and continue to introduce innovations that impact positively on the livelihoods of the poor.